Suicide risk and depressive symptoms among university students before and during social isolation due to COVID-19 (Research, Society and Development, 2023)
Objective: Examine associated factors with suicide risk and depressive symptoms among Brazilian college students before and during the isolation caused by COVID-19. Design and Methods: It was evaluated 102 university students. Data were collected before social isolation and during the initial phase of  isolation. Findings: The risk factors for both depression and suicide risk were: feeling lonely, entered the university through the quota system, started psychological or psychiatric treatment during the pandemic and  reported a history of emotional abuse in childhood and/or adolescence. Just for depression: studying full-time, self-declared white, started health treatment during social isolation and the initial phase of the pandemic. For suicide risk only: family income of up to three minimum wages and reported a history of physical neglect in childhood and/or adolescence. Conclusion: The findings provide support for educational restructuring strategies to reduce the risk of suicide and depression among university students.